2019
DOI: 10.3389/fnagi.2019.00206
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Curcumin and Piperine as Potent Acetylcholine and Amyloidogenic Inhibitors With Significant Neuroprotective Activity in SH-SY5Y Cells via Computational Molecular Modeling and in vitro Assay

Abstract: Hallmarks of Alzheimer’s disease (AD) pathology include acetylcholine (ACh) deficiency and plaque deposition. Emerging studies suggest that acetylcholinesterase (AChE) may interact with amyloid β (Aβ) to promote aggregation of insoluble Aβ plaques in brains of patients. Current therapeutic options available for AD patients, such as AChE inhibitors, provide only symptomatic relief. In this study, we screened four natural compounds believed to harbor cognitive benefits—curcumin, piperine, bacoside A, and chebuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 81 publications
(86 reference statements)
1
24
0
Order By: Relevance
“…AA is known to scavenge mitochondria-generated ROS [31], but the effects of SCE or AA on mitochondrial respiration in the brain has not previously been tested. Consistent with previous reports that combinations of plant extracts exhibit augmented biological activity compared with individual plant extracts [32,33], we found that a mixture of SCE and AA at a 4:1 ratio (10 µg/mL) exerted synergistic effects on mitochondrial respiration. However, this effect was absent at lower ratios of SCE in the mixture, implying that not only do SCE and AA in the mixture additively increase mitochondrial activity, the inclusion of AA may contribute to the scavenging of ROS, produced as a result of enhanced mitochondrial respiration.…”
Section: Discussionsupporting
confidence: 92%
“…AA is known to scavenge mitochondria-generated ROS [31], but the effects of SCE or AA on mitochondrial respiration in the brain has not previously been tested. Consistent with previous reports that combinations of plant extracts exhibit augmented biological activity compared with individual plant extracts [32,33], we found that a mixture of SCE and AA at a 4:1 ratio (10 µg/mL) exerted synergistic effects on mitochondrial respiration. However, this effect was absent at lower ratios of SCE in the mixture, implying that not only do SCE and AA in the mixture additively increase mitochondrial activity, the inclusion of AA may contribute to the scavenging of ROS, produced as a result of enhanced mitochondrial respiration.…”
Section: Discussionsupporting
confidence: 92%
“…One possibility is that analog 2 is induced to adopt the "correct" conformation when binding to both targets (i.e., 2f, Figure 2), and this structure fits well within the AChE active site but poorly within the BACE-1 active site, perhaps due to unfavourable interactions of the fluorine substituents of 2 with BACE-1 active site residues. A second possibility is that 2 adopts an "incorrect" conformation upon binding to both targets (e.g., 2a, Figure 2), and this novel molecular shape is readily accommodated by AChE [35] but not by BACE-1, perhaps due to different levels of flexibility within the enzyme active sites. A third possibility is that the analog 2 adopts different conformations upon binding to AChE vs BACE-1, since the microenvironments within the enzymes' active sites could be different (e.g., more/less polar), the "correct" binding geometry of 2 might be favoured in AChE but not in BACE-1.…”
Section: Biological Activity and Solubilitymentioning
confidence: 99%
“…The preparation of the optimal concentration of pure curcumin, piperine and their mixtures was performed based on an optimized protocol (Manap et al, 2019).…”
Section: Compound Preparationmentioning
confidence: 99%
“…We had previously reported on the Aβ inhibition and disaggregation assay of selected compounds by using Thioflavin T fluorescence assay (Manap et al, 2019). Thioflavin T (ThT) is a small molecule that emits strong fluorescence upon binding to amyloids (Xue et al, 2017).…”
Section: Aβ42 Fibrils Detection Using Thioflavin T Stainingmentioning
confidence: 99%
See 1 more Smart Citation